REQUIREMENTS FOR THE USE OF CASE TECHNOLOGY IN THE FORMATION OF INFORMATION COMPETENCE OF MATHEMATICS TEACHERS - Abdualiyeva Р.Е.; Seitova С.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article considers the issue of using case technologies for the development of information competence of teachers. The mastery of information and communication technologies by mathematics teachers is the formation of a natural –scientific worldview, the improvement of educational and cognitive activity. It promotes the development of a personality capable of adapting to new achievements of scientific and technological progress. Purpose: formation of information competencies of mathematics teachers through the effective use of the updated education system. Tasks: to determine the place of the case technology in the learning process and the requirements for its application; to give a characteristic. Information competence is an integral part of the development of a teacher’s competence in accordance with modern requirements. When forming information competencies, teachers, first of all, master the essence, possibilities and prospects of the psychological and pedagogical foundations of the use of ICT. Technologies occupy a special place in the learning process, in improving the quality of education. Teacher’s actions when using case technology: 1) Creative work on the selection of cases and questions (selection of situations on the topic, definition of goals and objectives, design and description of the situation); 2) teacher’s actions in the lesson (introduction, situation analysis, discussion, conclusion). Experimental work was carried out to determine the requirements for the use of case technology and a conclusion was formulated.